AI-Driven Digital Infrastructure and Infrastructure Innovation Systems: A Conceptual Analysis - Nguyen Minh Anh; Tran Quang Huy (Universitas Sains dan Teknologi Komputer, 2026)
The evolution of infrastructure development increasingly relies on integrating digital technologies to support complex, multi-actor innovation systems. Modern infrastructure projects involve governments, construction industries, research institutions, and technology providers, requiring efficient coordination, data integration, and collaborative decision-making mechanisms. This study examines the role of AI-Driven Digital Infrastructure in enhancing coordination and collaboration within Infrastructure Innovation Systems. A conceptual literature analysis was employed to synthesize prior research on AI applications, digital infrastructure, and innovation systems and map relationships between AI capabilities and systemic innovation dynamics. This study adopts a purely conceptual research design based on structured literature synthesis rather than empirical testing. Additionally, illustrative conceptual scenarios demonstrate potential coordination mechanisms that may facilitate information flows, inter-organizational alignment, and collective decision-making. The analysis suggests that AI-Driven Digital Infrastructure may function as a structural enabler contributing to institutional alignment, knowledge integration, and multi-stakeholder interaction within infrastructure ecosystems. The study provides a conceptual framework that links digital intelligence to systemic innovation processes, highlighting the role of AI as a backbone for coordination within complex infrastructure networks. This research contributes to theory by integrating perspectives from digital infrastructure, AI, and Infrastructure Innovation Systems into a unified analytical model. It offers conceptual insights to inform future research on digital infrastructure development.